Gamma-aminobutyric acid (GABA) production in fermented milk by lactic acid bacteria isolated from spontaneous raw milk fermentation. (April 2022) - Galli, Viola; Venturi, Manuel; Mari, Eleonora; Guerrini, Simona; Granchi, Lisa
Abstract: Lactic acid bacteria (LAB) may release bioactive compounds in fermented milk such as γ-aminobutyric acid (GABA) that have positive effects on human health. In the present work, from spontaneous raw milk fermentations 14 LAB strains belonging to 6 species were isolated. Their technological and nutritional characterisation led to the selection of two strains of Lactococcus lactis with a high GABA-producing capability in milk, enhanced by the addition of 5 mmol of monosodium glutamate (up to 249.31 mg L −1 ) and by co-culture with Lacticaseibacillus rhamnonus or Lacticaseibacillus paracasei. Fermented milks obtained by the two mixed starters ( Lc. lactis and L. rhamnonus or L. paracasei ) were characterised by a final GABA content of 185.81 ± 24.0 and 319.72 ± 27.15 mg L −1, respectively. GABA content increased during the storage, reaching 395.84 ± 12.55 and 377.49 ± 46.62 mg L −1 . In conclusion, the selected starters represent a natural tool for the production of fermented milk containing high GABA concentrations.